Quantum size effects of small, size-selected and deposited CoRh clusters on Ni - T Beeck; I Baev; K Chen; S Palutke; W Wurth; M Martins (New Journal of Physics, 2016)
The electronic, chemical and magnetic properties of in situ prepared, mass-selected and deposited Co _x Rh _y alloy clusters with up to five atoms per cluster have been studied by means of x-ray absorption and x-ray magnetic circular dichroism spectroscopy. The clusters were supported on a remanently magnetized Ni film. The cluster properties exhibit strong size and composition dependent effects. By alloying of pure Co _1,2 adatoms and dimers with Rh the chemical reactivity towards oxygen is significantly enhanced for specific compositions. The oxidation of the alloyed clusters strongly affects the magnetic properties which results in a reduction of the orbital and spin magnetic moments. The exchange coupling between the oxidized Co atoms and the Ni surface exhibits a size and a composition dependent oscillation between antiferromagnetic and ferromagnetic coupling.